Experimental Study on Heat Transfer Coefficients in an Office Room with a Radiant Ceiling During Low Heating Loads - Piotr Michalak (Energies)
Estimation of the heating or cooling capacity of radiant systems requires selecting appropriate internal heat transfer coefficients by convection (CHTCs) and radiation (RHTCs). Due to practical reasons, their measurement during the normal use of buildings is very troublesome. This study attempts to present the results of measurements of CHTCs and RHTCs taken in an office room located in a passive building with a heated concrete ceiling. Special attention was paid to the proper choice of reference temperatures. For better accuracy, view factors for radiant heat exchange were calculated using Matlab. Average values of CHTCs and RHTCs calculated from measurements amounted to 0.80 W/m2K and 5.66 W/m2K. RHTCs showed a significant correlation against the ceiling temperature, with the coefficient of determination being R2 = 0.96. Finally, the total heat transfer coefficient of 6.47 W/m2K was obtained. These values are comparable with other studies and standards and confirm that measurements were performed correctly.